Opportunities to Use the Clean Development Mechanism - Melgar, Carlos Quiroz (My University, 2012)
Climate change is forcing countries to increase their awareness and their actions to mitigate and/or adapt to the new situation. Recognizing their responsibility in the historical accumulation of anthropogenic greenhouse gases (GHG) in the atmosphere (widely accepted as the main cause of the global warming), most of the developed countries accepted binding targets for their emissions. To keep their emissions inside the limits or to offset their excess, these countries develop mitigation actions worldwide, which at the same time produce incomes through the transaction of carbon credits in the carbon markets. Peru is one of the countries were these mitigation actions are applied. The country has good potential to develop carbon projects in the energy and forest sectors, but the actions have been very limited until now: Peru only holds 0.7% of the total incomes generated. This thesis has the objective of analyzing and presenting the current situation of Peru as a host country of climate change mitigation actions financed by the carbon markets. Nowadays, the country has more information available than ever, but the independence of the involved sectors keep environmental, energy and investments information separated among them, making it difficult for investors to have a broad idea of the situation. Thus, this paper also aims to join dispersed research efforts in order to make visible the current state, the trends of investments, as well as the barriers and opportunities that the carbon markets face in Peru. As a result of the investigation, it was clarified that Peru’s industrial sector is small, being transportation sector the principal energy consumer and a potential area for developing carbon projects. Even though it’s relatively small size, the power sector offers profitable opportunities of investment, highly attractive to be complemented with incomes from carbon sales. Finally, the forest sector, which is Peru’s main source of GHG emissions due to deforestation, holds the largest potential for developing carbon projects by implementing reforestation and conservation actions. Forest projects are needed, not only due to the business opportunities, but to avoid destroying one of the most valuable resources of the country: its biodiversity.
Keywords: Maskinteknik; Energi; Mekanisk energiteknik; Mechanical Engineering; Energy; Mechanical energy engineering